An integrated model for vessel traffic and deballasting scheduling in coal export terminals. (August 2021) - Guo, Zijian; Cao, Zhen; Wang, Wenyuan; Jiang, Ying; Xu, Xinglu; Feng, Peng
Highlights: A novel integrated vessel traffic and deballasting scheduling problem is studied. Tidal fluctuation in the channel and vessel stability constraints are considered. An integrated scheduling model to avoid loading interruption and reduce vessel delay. Determine vessel sequences, lay-by berth allocation and deballasting plans simultaneously. A total weighted delay reduction of 20.84% can be obtained compared to rule-based methods. Abstract: Most bulk carriers arrive at coal export terminals (CETs) under empty or lightly loaded conditions. Ballast water, which is onboarded to maintain vessel stability during a voyage, must be pumped out as the cargo is loaded. As modern CETs are rapidly developing, vessels' deballasting capability is being updated too slowly and far behind the CET loading efficiency improvement. Therefore, an increasing number of vessels fail to finish deballasting in a timely manner, which results in frequent operational interruptions at the terminal. The high loading efficiency of modern CETs is discounted by a ship's deballasting capability. Conventionally, many CETs have allowed vessels to deballast in advance at anchorages or lay-by berths to avoid delays at the loading berth and wasted resources. In this sense, in addition to making a complex traffic-scheduling plan for vessels entering and leaving terminals, port managers must make proper deballasting plans for vessels and avoid excessive deballasting problems. However, research on vessel scheduling considering deballasting is limited to date. To fill this gap, this paper proposes an integrated scheduling model (ISM) that manages the scheduling process of vessel traffic and deballasting operations. Special considerations of vessel stability under deballasting and tidal influence are introduced. As a result, with the goal of minimizing the total weighted delay, the model can simultaneously optimize the vessel sequence, lay-by berth allocation, and deballasting plan. A series of comprehensive experiments was conducted based on practical data collected from a major CET in China. The performance of the proposed ISM was tested through comparisons of scheduling under common rule-based scheduling methods with varying traffic density and terminal efficiency properties. The results show that the ISM can avoid untimely deballasting, shorten the vessel port stay time, and directly contribute to a total weighted delay reduction of 20.84%. Application of the ISM to address the conflict of unbalanced machinery upgrades between CETs and vessels at various stages is of great importance to guarantee improved port efficiency.